Synthesis of green metaloxide nanoparticles using aloe-barbadensis leaf extract (Acid Red 28) for dye removal applications - Jamali, Abdul Rauf; Batool, Madhia; Asghar, Sajid Ali; Akhter, Faheem; Hussain, Fayaz; Khurshid, Shazia (Penerbit Universiti Kebangsaan Malaysia, 2022)
The present study focuses on the synthesis of stable metal oxide nanoparticles (MO-NPs) using Aloe Vera Barbadensis leaf extracts via a green route approach. The MO-NPs were synthesized by the interaction of Aloe-Barbadensis leaf extract with metaloxide salt and its azodye (Congo red). These NPs were then characterized using SEM (surface morphology), XRD (Crystallography structure, peaks of MO-NPs), UV-Vis (Absorption spectrum) and FTIR (presence of functional group). The SEM images revealed the surface morphology of nano sized powder while the XRD results showed that the particle size ranged between 5-30 nm. The UV-Vis absorption spectrum revealed that the MO-NPs are iron and copper oxide respectively. FTIR data, on the other hand, indicated the hydroxyl (OH) functional group stretching due to the presence of alcohols and phenolic chemicals in the extract. Moreover, the effect of physical properties such as solution concentration, their PH and MO-NPs adsorbent dosage on percentage of dye degradation was also determined. As per results, the NPs removed about 70-80% of Congo red dye solution at optimum condition of reaction factors. The dynamics of pseudo-second order was followed in the adsorption process by MO-NPs.